THE EFFECT OF LIFESTYLE POCKET MONEY AND ONLINE SHOPPING ON STUDENTS' CONSUMER BEHAVIOR - Diana Pangastuti, Margareta; Lika, Ernestina; Faisal Aksa, Adi (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This study aims to determine the effect of pocket money, lifestyle and online shop on the consumer behavior of FEB students at Timor University. The results of the simple linear regression analysis state that, partially the pocket money variable has a significant effect on the student's consumer behavior variable as indicated by a significant level of 0.000 <0.05. Partially the Lifestyle variable has a significant effect on student consumer behavior as indicated by a significant level of 0.000 <0.05. Partially the online shop variable has a significant effect on student consumer behavior as indicated by a significant level of 0.000 <0.05. Simultaneously the pocket money, lifestyle and online shop variables have a significant effect on student consumer behavior as indicated by a significant level of 0.000 <0.05.